The Economic Cost of Burnout in Veterinary Medicine - Neill, Clinton L.; Hansen, Charlotte R.; Salois, Matthew (Frontiers in Veterinary Science, 2022)
The purpose of this study is to estimate the economic cost of burnout in the veterinary profession and highlight the financial reasons why the industry should address the burnout crisis from an organizational perspective. Using data from 5,786 associate veterinarians in private practice, information was obtained using employment information related to compensation, work hours, hour preferences, and job turnover. Burnout was measured using the Professional Quality of Life Scale and used to calculate conditional probabilities on turnover and reduced working hours due to burnout. Lost revenue from each outcome (turnover and reduced working hours) was then used to calculate the economic costs to the veterinary services industry. The attributable cost of burnout of veterinarians to the US industry is between $1-2 billion annually in lost revenue, though there is a large amount of uncertainty. The cost is dependent on whether veterinary technicians are included in the analysis. The highest economic cost per veterinarian is among food animal practitioners, while the lowest is among equine. This study demonstrates that there are significant economic costs due to burnout among veterinarians and veterinary technicians. We suggest pursuing organizational interventions as these have shown the most impact in decreasing burnout and increasing satisfaction among human health physicians.